2019
DOI: 10.4103/bc.bc_1_19
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid therapy for vasculoprotection in acute ischemic stroke

Abstract: Uric acid (UA) is a product of the catabolism of purine nucleotides, the principal constituents of DNA, RNA, and cellular energy stores, such as adenosine triphosphate. The main properties of UA include scavenging of hydroxyl radicals, superoxide anion, hydrogen peroxide, and peroxynitrite that make this compound to be the most potent antioxidant in the human plasma. As the result of two silencing mutations in the gene of the hepatic enzyme uricase which degrades UA to allantoin, humans have higher levels of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 83 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Animal studies have demonstrated the causal relationship between systemic inflammation and AIS neurological damage and poor prognosis [ 29 ]. The underlying mechanisms of systemic inflammation affecting the poor prognosis of AIS include neutrophil infiltration, blood-brain barrier (BBB) destruction, and cerebral ischemia-reperfusion injury [ 30 , 31 ]. Animal experiments showed that reducing leukocyte infiltration could reduce the neurological damage of AIS and delay disease progression [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated the causal relationship between systemic inflammation and AIS neurological damage and poor prognosis [ 29 ]. The underlying mechanisms of systemic inflammation affecting the poor prognosis of AIS include neutrophil infiltration, blood-brain barrier (BBB) destruction, and cerebral ischemia-reperfusion injury [ 30 , 31 ]. Animal experiments showed that reducing leukocyte infiltration could reduce the neurological damage of AIS and delay disease progression [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that, compared with those in other animals, higher concentrations of uric acid in humans may stimulate the cerebral cortex to obtain more brain volume and better intelligence performance ( 49 ). The antioxidant, vasculoprotective, and neuroprotective effects of uric acid have also been proven to be effective in treating some neurological diseases ( 6 , 50 , 51 ). However, whole brain structural mapping in gout patient has not been done before.…”
Section: Discussionmentioning
confidence: 99%
“…Uric Acid is a product of the catabolism of purine nucleotides and contributes up to 60% of the plasma antioxidant activity: scavenging hydroxyl radicals, superoxide anions, hydrogen peroxide, and peroxynitrite (103). In MCAO mouse models, uric acid treatment reduced infarct volume, ROS production, and neurological deficits (104,105).…”
Section: Therapeutic Strategies Neuroprotection and Recanalization: Cmentioning
confidence: 99%
“…For example, in a rat MCAO model, uric acid treatment reduced MCA wall thickening and increased lumen expansion (106). Mechanistically, uric acid treatment increases the expression Kruppel-like factor 2 and reduces the expression of VEGF-A, thereby maintaining BBB integrity (103). In the URICO-ICTUS trial, a multicenter, randomized, double blind, phase 2b/3 trial, patients that received uric acid in combination with alteplase (<4.5 h) did not improve outcomes at 90 days, but in a sensitivity analyses, a borderline significance was seen in patients with uric acid treatment who experienced an ordinal shift in mRS, decreasing their residual disability by a median of 1 point on the mRS compared to the placebo group (107).…”
Section: Therapeutic Strategies Neuroprotection and Recanalization: Cmentioning
confidence: 99%